Application of Scholastic Test Using Computer Based Tests - Paramartha, Wayan Eka; Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2020)
The purpose of this study was to find a practical procedure in applying the CBT-based Scholastic Talent Test (Computer Based Test) at SMK Negeri 2 Singaraja. The method of this research is development research, namely the development of computer-based tests. There are three stages in this research, namely the preparation of a computer system, test calibration and utilization on a limited scale. The benefit of this research is that it can be used as an alternative to giving Talent Tests by the Guidance Counseling Teacher in providing talent-interest counseling services at the School. Then the use of computers as a substitute for tests that use paper and pencil becomes more efficient and effective.Â